PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN: (STUDI PADA PRODUK PREPAID TELKOMSEL DI KOTA BANDUNG) - Juhana , Dudung; Larashati, Irena (Majalah Bisnis & IPTEK, 2021)
This research aims to obtain empirical evidence and find clarity phenomenon along with conclusion about service quality influence toward Telkomsel prepaid produk customer satisfaction in Bandung. This research type is descriptive and verificative, and also using cross section approach. Data were analyzed by descriptive analysis and path analysis. The result of this research show that service quality is on good category and customer satisfaction is also on good category. From hypothesis testing result be found a significant simultaneously influence from service quality toward customer satisfaction a number of 67,6%. And for partially influence, tangible give an influence by 14,91%, emphaty give influence by 9,82%, responsiveness give an influence by 12,21%, reliability give an influence by 17,49%, and assurance give an influence by 13,14%. Thus Telkomsel prepaid produk need to increase service quality performance if they want to increase customer satisfaction. Keywords: service quality, customer satisfaction.